Shakespeare in Hindsight Counterfactual Thinking and Shakespearean Tragedy. - Khan, Amir (Edinburgh Critical Studies in Shakespeare and Philosophy Ser., 2017)
This bold new study uses counterfactual thinking to enable us to feel, rather than to explain, Shakespeare's tragedies.